Bite force evaluation in subjects with cleft lip and palate - Carla Renata Sipert; Ana Claudia Martins Sampaio; Inge Elly Kiemle Trindade; Alceu Sérgio Trindade Junior (University of São Paulo, 2009)
The purpose of this study was to evaluate the masticatory function of subjects with cleft lip and palate by analyzing the bite force developed by these individuals. Bite force was evaluated in a group of 27 individuals with repaired unilateral cleft lip and palate (14 males and 13 females - aged 18-26 years) and compared to the data achieved from a group of 20 noncleft subjects (10 males and 10 females - aged 18-26 years). Measurement was achieved on three positions within the dental arch (incisors, right molars and left molars), three times at each position considering the highest value for each one. Statistical analysis was performed by ANOVA and Mann-Whitney test ( α = 5%). There was a significant deficit in bite force in male individuals with cleft lip and palate compared to the male control group (p=0.02, p=0.004, p=0.003 for incisors, right and left molars, respectively). For the female group, the difference was not statistically significant (p=0.79, p=0.06, p=0.47). In the group of individuals with clefts, 92.6% were under orthodontic treatment, which could be a reason for the present findings, since it can decrease the bite force more remarkably in males than in females. In conclusion, the bite force is significantly reduced in men when comparing the cleft group to the noncleft group. In females, this reduction was not significant in the same way. However, the main reason for this reduction and for the different behavior between genders should be further investigated.